Can we use 2,3,5-Triphenyltetrazolium chloride-stained brain slices for other purposes? the application of western blotting - Sanchez-Bezanilla, Sonia (2020)
2,3,5-Triphenyltetrazolium chloride (TTC) staining is a commonly used method to determine the volume of the cerebral infarction in experimental stroke models. The TTC staining protocol is considered to interfere with downstream analyses, and it is unclear whether TTC-stained brain samples can be used for biochemistry analyses. However, there is evidence indicating that, with proper optimization and handling, TTC-stained brains may remain viable for protein analyses. In the present study, we aimed to rigorously assess whether TTC can reliably be used for western blotting of various markers. In this study, brain samples obtained from C57BL/6 male mice were treated with TTC (TTC+) or left untreated (TTC-) at 1 week after photothrombotic occlusion or sham surgery. Brain regions were dissected into infarct, thalamus, and hippocampus, and proteins were extracted by using radioimmunoprecipitation assay buffer. Protein levels of apoptosis, autophagy, neuronal, glial, vascular, and neurodegenerative-related markers were analyzed by western blotting. Our results showed that TTC+ brains display similar relative changes in most of the markers compared with TTC- brains. In addition, we validated that these analyses can be performed in the infarct as well as other brain regions such as the thalamus and hippocampus. Our findings demonstrate that TTC+ brains are reliable for protein analyses using western blotting. Widespread adoption of this approach will be key to lowering the number of animals used while maximizing data.